BREXIT AS A MANIFESTATION OF THE CRISIS OF LIBERAL DEMOCRACY IN THE UNITED KINGDOM - Савон, В. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
The publication is devoted to the analysis of the UK exit from the European Union as a manifestation of the systemic crisis of the liberal democracy model. The causes and difficulties of this process are analyzed under the conditions of the failure of the political system to make political decisions. The problematic issues of liberal ideology and the model of liberal democracy were examined. The differences in the ideological convictions of the two founders of liberalism – Thomas Hobbes and John Locke, as well as the role of these differences in the modern functioning of liberal democracy in the United Kingdom. The role of globalization processes in the world in the context of the development and functioning of liberal democracy is analyzed. Some features of the course of globalization processes in the world are highlighted. The features of the existence of the European Union as an international supranational organization in the context of its influence on the functioning and stability of the political system of the United Kingdom are examined. The features of the functioning of the model of liberal democracy under conditions of strengthening the international way of making political, economic and legal decisions are emphasized. Particular attention is paid to the political motives of organizing of start of the process of the UK’s exit from the European Union, as well as the consequences of such a decision. In addition, the role of populist movements in this process, that have Euro-skeptical positions, has been established. The features of the functioning of populist movements are highlighted. The essence of the crisis of the model of liberal democracy in the United Kingdom is determined. The author analyzes the risks of the United Kingdom leaving the European Union in the context of a peace settlement of the conflict in Northern Ireland as one of the indicators of the crisis of the liberal political system. In conclusion is performed analysis of some results of the referendum on the withdrawal of the United Kingdom from the European Union.